1994
DOI: 10.1073/pnas.91.26.12388
|View full text |Cite
|
Sign up to set email alerts
|

Stereospecific dihaloalkane binding in a pH-sensitive cavity in cubic insulin crystals.

Abstract: Crystallographic analysis at 2-A resolution of the selective binding of dihalogenated methane, ethane, and ethylene compounds in the cavity on the cubic insulin dimer axis provides a model for anesthetic-protein interactions. At pH 6-11, 1,2-dichloroethane binds isomorphically in the righthanded cis-conformation, displacing four water molecules from the invariant cavity. Lowering the pH to 5.7 in 1 M Na2SO4 without dihaloalkanes induces a cooperative structural transition in which the dyad cavities between B13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…All of the binding sites were predominantly apolar, although most also showed evidence of significant polar interactions between charged or polar amino acids and the polarizable halogen atoms, particularly the bromine. The possible importance of polar interactions between proteins and halogenated compounds has been noted before (3,28), and the likelihood that general anesthetic binding sites are amphiphilic in nature has been stressed by our group (29,30) and others (31)(32)(33).…”
Section: Resultsmentioning
confidence: 84%
“…All of the binding sites were predominantly apolar, although most also showed evidence of significant polar interactions between charged or polar amino acids and the polarizable halogen atoms, particularly the bromine. The possible importance of polar interactions between proteins and halogenated compounds has been noted before (3,28), and the likelihood that general anesthetic binding sites are amphiphilic in nature has been stressed by our group (29,30) and others (31)(32)(33).…”
Section: Resultsmentioning
confidence: 84%
“…These compounds are hydrophobic, like O 2 and CO, and have been demonstrated to bind to hydrophobic pockets within proteins such as insulin (Gursky et al, 1994). DCE and other organic halides were found to bind to the Xe4 cavity within wild type HbI-CO, as evident by positive features in F o organic -F o native difference electron density maps (see Figure 2D, Figures S1 and S2, and Tables S1-S3, Supplemental Data).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, anesthetics representing a range of chemical classes inhibit this enzyme with potencies that depend upon their hydrogen-bonding abilities. High resolution X-ray crystallographic studies of halogenated alkane binding to insulin dimers has provided direct structural evidence that favorable electrostatic interactions are strong enough to enhance binding affinity (Gursky et al, 1994). Manderson and Johansson (2002) showed that substituting tyrosine for tryptophan in a synthetic four-␣-helix bundle reduces the binding affinity of the inhaled anesthetics chloroform and halothane 6-and 3-fold, respectively, without significantly changing the protein's overall structure.…”
Section: Discussionmentioning
confidence: 99%